Abuse of anabolic steroids - Gök, Rahime; Yalçın, Ayşe Dilara; Tural, Ümit (Journal of Dependence, 2016)
Anabolic androgenic steroids (AAS) are synthetic derivatives of the natural male hormone testosterone. AAS are used as therapeutic purposes in the treatment of male hypogonadism, delayed puberty, suppression of lactation, postmenopausal libidinal loss, aplastic anemia, in cases of malnutrition and high catabolism and hereditary angioedema. On the other hand, AAS have been used illegally and unrestrainedly for decades by professional athletes to enhance performance, and especially by young men who want to have a more muscular appearance. Various studies from different countries showed the lifelong prevalence of AAS misuse in young men around 3-12%. There are many physical and psychological, acute or chronic side effects in patients due to the unrestrained AAS use. Further research is needed in this field because of the increase trend of AAS abuse in recent years. In this paper we aimed to review the research papers on AAS which has been not recognized yet sufficiently by clinicians.
Keywords: Anabolic steroids; abuse; dependency; prevalence